2023
DOI: 10.3390/medicina59040813
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Virtual Reality on the Limb Motor Function, Balance, Gait, and Daily Function of Patients with Stroke: Systematic Review

Abstract: Background and Objectives: This systematic review aimed to clarify the effectiveness of virtual reality rehabilitation on physical outcomes for people with stroke. Materials and Methods: Articles were searched through PubMed, EMBASE, the Cochrane Library, the Physiotherapy Evidence Database, CINAHL, Web of Science, and ProQuest Dissertations and Theses, from inception to 30 April 2022. Methodological quality was scored using the Assessing the Methodological Quality of Systematic Reviews 2 tool. Each systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…These findings aligned with those of several included studies [ 27 , 28 , 31 33 ]. Zhang et al [ 38 ] also reported that the upper limb function in the VR group outperformed that of the conventional method, with significant differences found between the 2 groups regardless of the intervention period. This was consistent with results from other included studies [ 27 , 28 , 31 33 ], which had varied intervention durations.…”
Section: Discussionmentioning
confidence: 99%
“…These findings aligned with those of several included studies [ 27 , 28 , 31 33 ]. Zhang et al [ 38 ] also reported that the upper limb function in the VR group outperformed that of the conventional method, with significant differences found between the 2 groups regardless of the intervention period. This was consistent with results from other included studies [ 27 , 28 , 31 33 ], which had varied intervention durations.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been a rapid increase in research and software development related to virtual reality (VR) rehabilitation, which combines VR technology and exercise [ 3 - 6 ]. There are two types of VR, namely non-immersive and immersive.…”
Section: Introductionmentioning
confidence: 99%